The Global Politics of Jazz in the Twentieth Century Cultural Diplomacy and "American Music" - Saito, Yoshiomi (Taylor & Francis, 2020)
From the mid-1950s to the late 1970s, jazz was harnessed as America's "sonic weapon" to promote an image to the world of a free and democratic America. Dizzy Gillespie, Dave Brubeck, Duke Ellington and other well-known jazz musicians were sent around the world - including to an array of Communist countries - as "jazz ambassadors" in order to mitigate the negative image associated with domestic racial problems. While many non-Americans embraced the Americanism behind this jazz diplomacy without question, others criticized American domestic and foreign policies while still appreciating jazz - thus jazz, despite its popularity, also became a medium for expressing anti-Americanism. This book examines the development of jazz outside America, including across diverse historical periods and geographies - shedding light on the effectiveness of jazz as an instrument of state power within a global political context.